Al-Quran Sebagai Sumber Hukum dalam Bacaan Kontemporer Muhammad Syahrur - Arip Purkon (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to examine the Koran as a source of law according to Muhammad Syahrur. The research conducted is a qualitative research with an ushul fiqh approach. The main data sources in this research are books written by Muhammad Syahrur. And secondary data sources in this study are scientific writings related to the themes discussed. This study concludes that according to Syahrur, the interpretation of the Koran must be carried out by people who are experts in their respective fields and in accordance with current scientific developments. Besides that, it is also necessary to sort out and re-select Islamic teachings from the Koran which is the object of ijtihad. Treatise verses are verses related to law or things that cannot be changed. The nubuwwah verses are verses whose interpretation is in accordance with the times. The Koran sets limits in establishing laws that cannot be violated.